KARAKTERISTIK KLINIKOPATOLOGI KANKER PAYUDARA DI SENTRA DIAGNOSTIK PATOLOGI ANATOMI FK UNAND TAHUN 2018-2021 - Naqia, Masyithah; Darwin, Eryati; Tofrizal, Tofrizal (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Breast cancer is a malignant tumor originating from the breast ductal and lobules epithelium. Clinicopathological factors in breast cancer such as age, sex, location, laterality, histopathological type, grade, and lymphovascular invasion are known affect the prognosis. Objective: This study aims to determine the clinicopathological characteristics of breast cancer at diagnostic center of anatomical pathology, Faculty of Medicine, Andalas University in 2018-2021. Methods: This study was descriptive observational with total sampling technique from medical records. Samples included all breast cancer patients in 2018-2021 who were fulfilled inclusion criteria, with total 334 samples. Results: The results showed that the most age group was ≥ 40 years (83.5%), the most common primary tumor site were other parts where 91% were overlapping lesions (34,1%), breast cancer was more common in the right breast (49.4%). Most of the histopathological types were invasive carcinoma mammae of NST (66,6%), with the majority being grade II (80%), and negative lymphovascular invasion in 63,7% of the samples that included the lymphovascular invasion examination. Conclusion: The conclusion of this study is that the majority of breast cancer cases at the diagnostic center of anatomical pathology, Faculty of Medicine, Andalas University, for 2018-2021 are in grade II, early detection needs to be done so that breast cancer can be diagnosed at an early stage.